Predicting couple satisfaction: the role of differentiation of self, sexual desire and intimacy in heterosexual individuals - Ferreira, Luana Cunha (2014)
Differentiation of self the ability to emotionally self-regulate and to maintain a sense of autonomy within a deep intimate relationship has been proposed as a relevant factor in couple satisfaction, but the mechanisms underlying this association remain unclear. Sexual desire and intimacy have recently drawn increased attention due to the proposal that some of the relational benefits of long-term intimacy (e.g., predictability) might be detrimental to desire and satisfaction. This study aimed to test a model illustrating the role played by differentiation of self in couple satisfaction through the underlying mechanisms of sexual desire and intimacy, in a survey of 428 heterosexual individuals. The findings supported the proposed model, suggesting that differentiation of self is a predictor of desire, intimacy and couple satisfaction. Desire mediated the association between differentiation and couple satisfaction, and also the association between differentiation and intimacy. Intimacy mediated the association between desire and satisfaction. The model was sustained for women, but a different mechanism was found for men. The results provide support for the close association between intimacy, sexual desire and satisfaction, while suggesting that differentiation of self has a fundamental role in sexual desire, intimacy and couple satisfaction.